Regional Impacts of High Speed Rail in China : Spatial Proximity and Productivity in an Emerging Economy - Jin, Ying; Bullock, Richard; Fang, Wanli (World Bank, Beijing, 2014)
This paper contains an initial reconnaissance of the situation in Yunfu, prior to the NanGuang project construction. It provides a brief overview of the trajectory of economic development in Yunfu from an economy that was dominated by primary industries to that by secondary industries. The development of local transport infrastructure is reviewed, as is the more detailed structure of local industries, with special emphasis on dominant industrial sectors and the planned industrial parks. The experience of high speed rail development impact elsewhere was drawn upon to reflect on the possible regional economic outcomes that might emerge following the opening of the Nanning-Guangzhou high speed rail. The structure of and the approach to a before and after monitoring study is considered. The remainder of the paper is divided into six parts. Part two gives a brief overview of the economic development in Yunfu municipality since its establishment in 1994. Part three describes local transport links and infrastructure. Part four provides a description of the internal structure of local industries, with special emphasis on the dominant industrial sectors and the planned industrial parks. Part five discusses possible regional economic impacts associated with the forthcoming high-speed rail line and part six summarizes a proposal for the next steps.